Orofacial clinical-radiological features of McCune-Albright syndrome in an adult: a case report - Ramírez Suarez, Reynier (2024)
Fibrous dysplasia is a benign and progressive bone disease of genetic basis that can affect one or several bones. Its high incidence in the pediatric age served as a basis for it to be previously considered exclusive to this stage; however, there are reports to date that show its development and later growth in the second decade of life. When associated with endocrine imbalances and café-au-lait spots, it is part of the McCune-Albright syndrome. The present case report shows the clinical and radiologic features of the oral-facial region of an adult patient with McCune-Albright syndrome. Lesions in the jaws affect the morphology and cause dysfunction. At the dental level, the changes produced result in malocclusion and structural defects. Radiological studies showed changes with mixed density and ground glass pattern.